2014
DOI: 10.1590/1983-1447.2014.04.45820
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the family in hospital-based palliative cancer care: perspective of nurses

Abstract: The objective was to understand the perspective of nurses about the participation of the family in palliative cancer care and to analyze the nursing care strategies to meet their needs. Descriptive and qualitative research, conducted at the National Cancer Institute between January and March 2013, with 17 nurses. Elements of the Roy Adaptation Model were used for the interpretation of the data. Two categoriesemergedfrom the thematic analysis: perspective of nurses about the presence and valuation of family in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 8 publications
0
36
0
7
Order By: Relevance
“…The healthcare professionals considered relatives as an asset for the healthcare system and a support for them (Da Silva & da Silva Lima, ; Ekstedt et al., ). Relatives were seen as a help for the healthcare professionals by recognising the daily needs of the patients (Effendy, Vernooij‐Dassen et al., ; Effendy, Vissers et al., ) and attending to daily care (Da Silva & da Silva Lima, ). Thus, relatives also learned about basic care (Da Silva & da Silva Lima, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The healthcare professionals considered relatives as an asset for the healthcare system and a support for them (Da Silva & da Silva Lima, ; Ekstedt et al., ). Relatives were seen as a help for the healthcare professionals by recognising the daily needs of the patients (Effendy, Vernooij‐Dassen et al., ; Effendy, Vissers et al., ) and attending to daily care (Da Silva & da Silva Lima, ). Thus, relatives also learned about basic care (Da Silva & da Silva Lima, ).…”
Section: Resultsmentioning
confidence: 99%
“…The critical appraisal demonstrated that some of the studies using quantitative methods did not have a representative sample of participants (Effendy, Vernooij‐Dassen et al., ; Eriksson & Lauri, ), the patients were not at similar point in the stage of their illness (Effendy, Vernooij‐Dassen et al., ; Effendy, Vissers et al., ), the confounding factors were not identified in the study (Kuuppelomäki, ; Zhang et al., ), and the outcomes of the study were not assessed using objective criteria (Effendy, Vernooij‐Dassen et al., ; Effendy, Vissers et al., ; Kuuppelomäki, ; Pardon et al., ; Zhang et al., ). In most of the qualitative studies evaluated, the philosophical perspective was not stated (Andershed & Ternestedt, ; Da Silva & da Silva Lima, ) and the influence of the researcher on the research was not addressed (Andershed & Ternestedt, ; Da Silva & da Silva Lima, ; Ekstedt et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Family members are often the main caregivers, who experience situations of pain, anxiety and the potential loss of a loved one. This group is essential to support the patient, but it is also impacted by the disease, and their suffering must also be addressed and relieved 6 . …”
Section: Introductionmentioning
confidence: 99%
“…In the hospital environment, it is relevant for the elderly to have them nearby for comfort and safety. A plan of directed nursing interventions and guiding can corroborate the family member's balance and ways of adapting to the reality that he or she experiences [12][13].…”
Section: Discussionmentioning
confidence: 99%